Pemanfaatan Limbah Biji Alpukat (Persea americana Mill) untuk Produk Modest Couture - Adhindha Firdausa Ratnasari; Kahfiati Kahdar; Imam Santosa (JURNAL RUPA, 2019)
Indonesia is one of the countries that has a major contribution to the total production of avocados (Persea americana Mill) in the world with a total production of 334,047 tons (5.64%) in 2017. So far, only the flesh of avocados are used for consumption, this causes waste from avocado seeds to accumulate with low utilization. In fact, avocado seed extract contains tannin which can be used as natural dyes for textile. This research aims to utilize avocado seed extract for coloring and creating motifs on silk fabric, as well to apply them in creating modest couture products. Modest couture is one of modest fashion markets which is couture. The consumers spend around US$ 270 billion in 2017 and it is estimated to reach US$361 billion in 2023, so it is expected that the use of avocado seed waste can be used regularly on a broad market, especially in Indonesia. In this study, the emphasis is on the different colors and motifs that can be produced through natural dyes from avocado seed extract, then proceed with designing the modest couture product according to the couture fashion criteria and the observation results of the existing couture products.